2020
DOI: 10.3390/antiox9111066
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and Metabolic Impact of Functional Foods with Antioxidant Properties Based on Whey Derived Proteins Enriched with Hemp Seed Oil

Abstract: The impaired ability to feed properly, evident in oncologic, elderly, and dysphagic patients, may result in malnutrition and sarcopenia. Increasing the consumption of dietary proteins by functional foods and enriching their composition by adding beneficial nutrients may represent an adjuvant therapy. We aimed to evaluate the safety and the positive effects of a standard diet (SD) supplemented with whey-derived protein puddings (WDPP), with appropriate rheological properties, and hemp seed oil (HSO), rich in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…After cooling to room temperature, 1 µL of the pyridine solution of TMS derivatives was injected. The GC-MS program used for this purpose was identical (70(0 )/5 • C min −1 /315 (30 )) to the one used to record the original sample prior to silylation, but also included a 7 min delay (the time that elapsed after the injection until the MS detector turn on).…”
Section: Gc-ms Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…After cooling to room temperature, 1 µL of the pyridine solution of TMS derivatives was injected. The GC-MS program used for this purpose was identical (70(0 )/5 • C min −1 /315 (30 )) to the one used to record the original sample prior to silylation, but also included a 7 min delay (the time that elapsed after the injection until the MS detector turn on).…”
Section: Gc-ms Analysesmentioning
confidence: 99%
“…Fotschki et al [ 29 ] reported that hemp seed oil induced oxidative stress in livers of obese rats, while in healthy rats it positively affected the antioxidant status. The use of whey-derived proteins enriched with hemp seed oil in the rats’ diet led to a reduction of oxidative stress marker in post-ischemic heart samples [ 30 ]. Toxic effects of copper in fish were overcome by application of dietary hemp seed oil, which was explained by a prooxidant–antioxidant balance at ω-3 and ω-6 fatty acid levels [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Paste meals contain a relatively large amount of water to enable stirring and swallowing; consequently, substantial amounts of ingredients decreased, leading to reduced energy and protein intake. A previous study suggested that adding oil to food could be an alternative nutritional method for patients with dysphagia [ 35 ], as lipids are high in calories, and suitable for adjusting the rheological properties of foods [ 35 ]. Further studies are needed to verify the effect of adding oil to food.…”
Section: Discussionmentioning
confidence: 99%
“…Monoecious varieties of industrial hemp are more prevalent by plant breeding, particularly those cultivated in Europe. Due to its antioxidant and antimicrobial properties, it is also used as an active ingredient in commercial insect repellents and biopesticides [ 5 , 6 ]. Hemp has the highest Young’s modulus values of any natural fiber and is the strongest cellulose fibers.…”
Section: Introductionmentioning
confidence: 99%